(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article presents a comprehensive scientifically based methodology for using a variety of visual and practical materials in inclusive biological education, developed on the basis of modern principles of universal education design and taking into account the individual characteristics of the perception and processing of information by various categories of students. A large-scale study conducted in 2022-2024 with the participation of 285 students with different educational needs and 38 experienced teachers from 18 educational institutions of various types, demonstrates the high effectiveness of a systematic multisensory approach to the organization of the educational process in the field of biological sciences. The developed and experimentally tested methodology includes detailed systematized recommendations for the professional adaptation of visual, tactile, auditory and kinesthetic materials for effective teaching of students with various educational needs, including sensory impairments, cognitive features and motor limitations. The results of a comprehensive longitudinal analysis show a statistically significant increase in the quality of assimilation of biological knowledge by 62%, a significant improvement in practical research skills by 58% and a significant increase in the level of active involvement in the educational process by 71%. Particular attention in the study is paid to the creation and practical implementation of a multi-level system of didactic materials, taking into account the cognitive, sensory and physical characteristics of students with disabilities and special educational needs of various etiologies and severity.